URGENSI PENDIDIKAN PERLINDUNGAN HUKUM UNTUK ANAK SEKOLAH - FISKA SIMBOLON, DEWI (Ensiklopedia Education Review, 2019)
The practice of national education is held by referring to certain juridical grounds that have been established, both in the form of laws and government regulations regarding education. Educational goals that educate the life of the nation. Children are the assets of the nation, education is also an asset of the nation but in other terms quality education will bring a nation to progress. As with children, the better the quality of children will bring a nation to progress. This makes education and children two things that are interrelated with each other. Article 28 B paragraph (2) of the 1945 Constitution affirms that: